Peran PBB dalam Mengatasi Konflik Kashmir : Tinjauan Hukum Internasional dan Strategi Resolusi Konflik - Avrilly, Aura Dwiayu; Gustianti, Nurbani Adien (Jurnal Ilmiah Wahana Pendidikan, 2025)
The Kashmir conflict is one of the most complex and enduring territorial disputes in international relations. This journal analyzes the role of the United Nations (UN) in efforts to resolve the Kashmir conflict, with a focus on international legal review and conflict resolution strategies. Through an analysis of UN documents, academic literature, and case studies, this research investigates the effectiveness of UN intervention from the beginning of the conflict to the present. The review of international law includes an analysis of UN resolutions related to Kashmir, relevant principles of international law, and the legal status of the disputed territory. The conflict resolution strategies implemented by the UN, including mediation, ceasefire monitoring, and confidence-building efforts, are critically evaluated. The findings show that although the UN has played an important role in easing tensions and preventing the escalation of conflict, the organization faces significant challenges in achieving a comprehensive and sustainable resolution. The effectiveness of the UN's role has been limited by factors such as the polarization of the parties' positions, the involvement of external powers, and changes in regional geopolitical dynamics. The study concludes with recommendations for a more holistic and adaptive approach to UN engagement in Kashmir, taking into account the complexity of the conflict and contemporary developments in international relations.